Optimizing Notary's Role in Creating Marriage Agreements in Pekanbaru After Constitutional Court Decision No. 69/PUU/XIII/2015 - Nadilla Aprilya; Satrio Abdillah (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
Constitutional Court Decision No. 69/PUU-XIII/2015 has brought about a significant paradigm shift in Indonesian marriage contract law, allowing for the creation of such contracts during the course of a marriage. This change necessitates a shift in the role of notaries from mere document creators to active and responsive legal educators. However, implementation in the city of Pekanbaru shows that the optimization of this role has not been fully achieved, marked by low legal literacy among the public, structural barriers, and the lack of integration between the notarial service system and regulations and technology. The main problem is the passive attitude of Notaries, who only respond to requests without proactively providing legal education. This empirical legal research aims to analyze and formulate a concept for optimizing the role of notaries in the creation of authentic marriage agreements following the Constitutional Court's decision in Pekanbaru. Using a sociological-legal approach with qualitative methods, this research is descriptive-analytical and exploratory in nature. Data collection was conducted through in-depth interviews, participatory observation, and focus group discussions, as well as document and literature studies. The research results indicate an increase in the creation of marriage agreement deeds following the Constitutional Court ruling, but the number remains low compared to the total number of marriages. The majority of clients come from highly educated groups and have economic-business motivations. The main challenges include inconsistent technical regulations, insufficient socialization, variations in notarial practices, and ineffective third-party protection mechanisms. As an innovation, this study proposes a model for transforming the role of notaries into a proactive-educational, inter-institutional collaborative, and digitally adaptive role. This model is expected to strengthen the position of notaries as an essential legal profession in protecting marriage law in Indonesia.